Effectiveness of a Stepped, Collaborative, and Coordinated Health Care Network for Somatoform Disorders (Sofu-Net): A Controlled Cluster Cohort Study. Issue 9 (November 2017) - Löwe, Bernd; Piontek, Katharina; Daubmann, Anne; Härter, Martin; Wegscheider, Karl; König, Hans-Helmut; Shedden-Mora, Meike
ABSTRACT: Objective: Stepped, collaborative, and coordinated approaches have been proposed as the optimal treatment strategy for somatic symptom and related disorders, but evidence supporting this strategy is lacking. The aim of this study was to assess the effectiveness of a guideline-based health care network for patients who are at high risk of somatoform disorder ( Sofu-Net ). Methods: In a controlled, prospective, observer-blinded cluster cohort study, patients who were at high risk of somatoform disorder were recruited at 18 primary care practices in the Sofu-Net and at 15 primary care practices that provided care as usual ( CAU ). The primary outcome at 6-month follow-up was the rate at which the patients received mental health treatment since the establishment of Sofu-Net. The secondary outcomes included the patients' clinical symptom severity. Results: A total of 119 patients in the Sofu-Net intervention group and 100 patients in the CAU control group who were at high risk of somatoform disorder were followed for 6 months. A significantly greater proportion of Sofu-Net patients than CAU patients received mental health treatment (47.9% versus 31.0%; odds ratio = 1.96; 95% confidence interval, 1.07–3.58). However, the Sofu-Net group did not show greater reductions in clinical symptom burden compared with the CAU group. Conclusions: The treatment of somatoform disorders within a guideline-based health care network resulted in increased rates of mental health treatment but failed to improve patient clinical outcomes. Future investigations are needed to investigate the combined value of health care networks with specialized psychotherapy interventions in patients at high risk of somatic symptom and related disorders. Trial Registration: ISRCTN55870770.